Lars Breuer - the love of the gods - Énard, Mathias 1972-; Schmidt, Sabine Maria 1968- (DCV, 2022)
The art of Lars Breuer (b. Aachen, 1974; lives and works in Düsseldorf and Cologne) is set apart by its broad spectrum of systems of reference. In his large-format installations, text-based works in his own typography draw connections to literature and art history. They are complemented by figurative and abstract paintings and photographs. In The Love of the Gods, Breuer presents 104 C-prints of photographs for which he pointed the camera’s lens into the barrels of disused rifles, pistoles, revolvers, and cannons. The pictures were taken on the artist’s travels to Athens, Bangkok, Buenos Aires, Copenhagen, Leverkusen, Ingolstadt, Melbourne, New York, Oslo, and Phnom Penh, in museums, palaces, and public squares. Breuer’s conceptual and meticulously sober-minded approach yields almost abstract compositions showing nothing but the round muzzles and the dark interiors of the weapons on a deep-black ground. We see only a ring-shaped ornament until it dawns on us that it is part of a lethal implement. A cruel constant of human existence stares us in the face: humans behind these weapons were perpetrators, humans in front of these weapons were victims. Lars Breuer’s turn the spotlight on what the aura of the ornaments conceals: they have wrought death
Impressum: Dieser Katalog erscheint anlässlich der Ausstellung "Lars Breuer - The Love of the Gods" im Kunstverein Leverkusen Schloß Morsbroich e.V., 17. September - 16. Oktober 2022
Keywords: Breuer, Lars -- 1974-; Schusswaffe; Fotografie; Abstrakte Kunst; Lars Breuer; Typografie; Matthias Enárd; Kunstverein Leverkusen Schloß Morsbroich e.V.; Deutsche Künstler; Sabine Maria Schmidt; Zeitgenössische Kunst; Ausstellungskatalog -- Kunstverein Leverkusen Schloß Morsbroich -- 17.09.2022-16.10.2022 -- Leverkusen; Bildband